Job engagement, job satisfaction, perceived job stress, affective organizational commitment and individual work performance: the case of Sibu Resident and District Office (RANDO) / Joycelyne Anak Nyandang ... [et.al] - Nyandang, Joycelyne; Jimmy Jalil, Laura Singgok (2019)
Without competent workforce, it is impossible for organization to outdo their competitors in today's highly competitive and robust work environment. Employees are expected to be proactive and fully committed. As such, the basis of this research is to examine the relationship between Job Engagement, Job Satisfaction, Perceived Job Stress, Affective Organizational Commitment and Individual Work Performance: The Case of Sibu Resident and District Office (RANDO).